Functional genetic analysis of the Eucalyptus grandis cellulose synthase 1 (EgCesA1) gene in Arabidopsis thaliana - Naidoo, Sanushka (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2009.